Possible roles of Juvenile Hormone and Juvenile Hormone binding protein on changes in the integument during termination of larval diapause in the bamboo borer Omphisa fuscidentalis - Eakartit Ritdachyeng (2018)
To understand the role of Juvenile Hormone (JH) on changes in the integument of Omphisa fuscidentalis Hampson (Lepidoptera: Pyralidae) during larval-pupal development, the expression patterns of transcripts of the O. fuscidentalis JH binding protein gene (OfJHBP) are determined in the integument of diapausing larvae. Quantitative real-time polymerase chain reaction (qRT-PCR) studies show that the relative levels OfJHBP mRNA in the integument do not differ significantly in different segments of the body. Application of the JH analogue (JHA) methoprene to diapausing larvae results in a relatively low expression of OfJHBP mRNA from days0 to 8 after JHA application and reaches maximal levels in the pupal stage. Changes in OfJHBP expression after 20-hydroxyecdysone (20E) injection also show low levels of OfJHBP mRNA from days0 to 8 and show a peak of expression in the pupal stage. Incubation of the integument in vitro in the presence of JHA (3.22μm) induces high levels of OfJHBP expression within 120min, whereas incubation with 20E (2.08μm) induces gene expression at 150min. To study the cooperative effect on OfJHBP expression of these two hormones, dose-response experiments are performed. Larval integument is maintained in the presence of 0.32μm JHA or 2.08μm 20E or a combination of both hormones in vitro for 120min. Induction of OfJHBP expression by JHA and 20E in combination is significantly higher than that of either hormone alone. The results impact not only on our understanding of how methoprene (and hence JH) terminates larval diapause through an increase in ecdysteroid titre in the haemolymph, but also on how JH acts directly on the integument to stimulate the expression of a JH binding protein gene. © 2013 The Royal Entomological Society.